PENGAWASAN PEMERINTAH DAERAH TERHADAP ILLEGAL FISHING ( Studi Kasus Kabupaten Rokan Hilir Provinsi Riau Tahun 2012 ) - Sofwan, Muhammad; ", Ishak (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Illegal fishing in Rokan Hilir’s sea was usual happened. The actors some from foreign fisherman, out-region fisherman, al though itself Rokan Hilir fisherman. Some of boat caughted are have not license and did the catch’s fish as illegal. Beside this, them also used catch’s tool was dangerous like trawl net who are explicit forbid in regulation Undang-Undang Perikanan Nomor 45 Tahun 2009 about perubahan Undang-Undang Nomor 31 Tahun 2004 was regulated about prohibit used catch’s tool is not friendly area. Refunctionalization of the verdict, make not wary effect to the actors, until the problems of illegal fishing was be caused in marine and fisheries sector able not be used optimally.Purpose of the research is to answer the problems was exist in this research that is the first, to find out the implementation of the control from local government about illegal fishing at Rokan Hilir sea, the secondly is to knowing the factors of barriers control the implementation of local government about illegal fishing practice. Type of this research is a qualitative research method. The location of this research is Kabupaten Rokan Hilir Provinsi Riau. Data colletion techniques are observation, documentation studies and field studies (interviews) where as analyzed the data were analyzed descriptively.The study findings indicate that the implications of the implematation control of Kabupaten Rokan Hilir Local Government that delegated to the Department of marine and fisheries Kabupaten Rokan Hilir as co-administration has not given the intensive control that the maximum for tackling and prevention of illegal fishing. In this context be happen now is by glow the action illegal fishing practice in Rokan Hilir sea indicate that a minimum of eforts the local Government for the controls implementation, especially for preventive and corrective character the control. Beside this increasing of controls coordination among instances is also important necessary to tackling the illegal fishing.Key Word : Pemerintah Daerah, Pengawasan, Illegal fishing.